2010
DOI: 10.1155/2010/817580
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Vaccination in Chronic Hepatitis B: Preclinical Studies in the Woodchuck

Abstract: Recommended treatment of chronic hepatitis B with interferon-α and/or nucleos(t)ide analogues does not lead to a satisfactory result. Induction of HBV-specific T cells by therapeutic vaccination or immunotherapies may be an innovative strategy to overcome virus persistence. Vaccination with commercially available HBV vaccines in patients did not result in effective control of HBV infection, suggesting that new formulations of therapeutic vaccines are needed. The woodchuck (Marmota monax) is a useful preclinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 187 publications
(250 reference statements)
0
10
0
Order By: Relevance
“…HBV DNA immunization is a promising strategy for inducing strong CD8 + T cell-mediated immunity in mice [18] , [19] , [20] , [21] , whereas this effect has been only transient and weak in clinical trials [22] , [23] . To move beyond various approaches already employed to improve DNA vaccination, we have explored the use of novel adjuvants that would specifically potentiate the Tc1 and/or Tc17 type of T cells as a means to overcome the problem.…”
Section: Introductionmentioning
confidence: 99%
“…HBV DNA immunization is a promising strategy for inducing strong CD8 + T cell-mediated immunity in mice [18] , [19] , [20] , [21] , whereas this effect has been only transient and weak in clinical trials [22] , [23] . To move beyond various approaches already employed to improve DNA vaccination, we have explored the use of novel adjuvants that would specifically potentiate the Tc1 and/or Tc17 type of T cells as a means to overcome the problem.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the functional defects of antigen-presenting cells, such as DCs, may cause the impaired T cell response during HBV infection. 22,85 Although treatment regimens for chronic hepatitis B have markedly improved outcomes during the last decade, the need for immune system activation to effectively induce sustained off-treatment disease remission and clearance of the hepatitis B surface antigen ('functional cure') still remains a largely unachieved target. 86,87 The host immune system plays a dominant role in the elimination of HBV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies may be needed to adjust the dose and timing of the booster doses to give a sustained immune response. Engaging therapeutic hepatitis B vaccines is a new approach against hepatitis B infection [19,20]. The cytokines (IFN-γ, TNFα, IL-2 and CD69) in CD4+ and CD8+ cells perform a vital role in various stages of viral infection [21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%